Correlation Between Depression And Blood Pressure In Eldery At St. Yosef Nursing Home Surabaya - Gozali, Ferry S; Sarvasti, Dyana; Isbandiati, Endang (JOURNAL OF WIDYA MEDIKA JUNIOR, 2019)
Introduction: Population of elderly in Indonesia is increasing every year, it’s caused by success of development in many sectors, especially health sector. Elderly will undergo process of degeneration which affect their health. Many factors can affect their health, one is mental health. Depression is the most common mental health problem faced by the elderly. Elderly have a greater risk of depression than younger adults. In depressed patients there are changes in the levels of hormones and neurotransmitters in the body. It can cause changes in organ function one of which is the change in blood pressure. Aim: The purpose of this study is to find the correlation between depression and blood pressure in the elderly in St. Yosef nursing home. Methods: This study uses an analytic study with the cross-sectional design and then analyzed using the Spearman test. This research was conducted in St. Yosef nursing home Surabaya on June 16, 2016 until June 19, 2016. The population of this study is 140 people. 46 of the 140 respondents are respondents who comply the criteria. Result: Thirty seven (37%) were diagnosed as mild depression, eigth point seven (8,7%) were diagnosed as severe depression, and twenty three point nine (23,9%) were diagnosed as hypotension. Respondent with depression (mild and severe) and hypotension is seventeen point four (17,4%). Statistical test using Spearmen corellation test shows a significant result with p=0,048 Conclusion: The result showed significant, so it can be concluded there is a correlation between depression and blood pressure in the elderly.